Tracing the development of public finance themes from Islamic perspective: a systematic literature review (SLR) Analysis - Mohd Thas Thaker, Hassanudin; Syed Salleh, Sharifah Nabilah; Duasa, Jarita; Siddiq, Muhammad Rizky; Taghizadeh-Hesary, Farhad (Springer Nature Singapore, 2025)
In this chapter, we carry out a joint methodology known as systematic literature review (SLR) and bibliometric analysis on articles published in the field of public !nance and Islamic economics from 1972 to 2022. We have utilized Scopus and other published reports in this field of research such as journal article, book chapter, conference paper, magazine, government reports, book, and review manuscript. We have pinpointed the major themes, important works, and emerging trends that are influencing Islamic public finance research nowadays. Our findings demonstrate a growing body of research that is dedicated to investigating alternative frameworks that are consistent with moral and religious principles. This interest in incorporating Islamic principles into public finance is evident. This study lays the groundwork for future research that unites Islamic economic concepts with traditional public finance theories, in addition to deepening our grasp of the academic discourse.